Effect of Preventive Hormonal Therapy on Breast Density: A Systematic Qualitative Review - Virginie Lienart; Birgit Carly; Xin Kang; Laura Guzy; Anna-Maria Sajovitz; Fabienne Liebens (The Scientific World Journal)
Breast density (BD) is recognized as one of the strongest independent risk factors of breast cancer (BC). Unlike most other risk factors, BD can be modified, suggesting that it may be a biomarker for preventive interventions. We conducted a qualitative systematic review to address the effect of preventive hormonal therapy on BD. Among the 26 relevant studies, 10 assessed the effect of tamoxifen on BD (TAM: n=2 877), 9 that of raloxifene (RLX: n=1 544), and 7 that of aromatase inhibitors (AI: n=416). The studies were characterized by a large heterogeneity in designs and in methods of BD measurement. BD could be reduced by TAM (10 studies/10). However, the effect of RLX and AI on BD remains unclear due to conflicting results between studies. Consequently, it is crucial to develop practical, accurate, and reproducible methods of measurement in order to be able to compare the effect of preventive hormonal agents on BD and to determine whether change in BD can be used as a predictor of response to therapy.